2015
DOI: 10.1007/s13592-015-0402-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of overwintering gene expression in the small carpenter bee, Ceratina calcarata

Abstract: Genome-wide overwintering gene expression studies in bees are of critical importance to understand their survival, life cycles, and fitness. In this study, we use RNA sequencing to characterize the genes and gene functions associated with overwintering adult females compared with active season females for the small carpenter bee, Ceratina calcarata. We found extensive changes in gene expression associated with overwintering, including an underrepresentation of genes related to muscle fibers and an overrepresen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Phosphorylation of perilipin is essential for the mobilization of fats in adipose tissue ( Beller et al 2010 ). Past studies have implicated lipid storage and metabolism as key to overwintering physiology in this and other Hymenopteran species ( Strassmann et al 1984 ; Toth et al 2009 ; Wasielewski et al 2014 ; Durant et al 2016 ). Moreover, previous studies have linked honey bee immune status to lipid store gene expression profiling ( Mao et al 2013 ; Salmela et al 2015 ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Phosphorylation of perilipin is essential for the mobilization of fats in adipose tissue ( Beller et al 2010 ). Past studies have implicated lipid storage and metabolism as key to overwintering physiology in this and other Hymenopteran species ( Strassmann et al 1984 ; Toth et al 2009 ; Wasielewski et al 2014 ; Durant et al 2016 ). Moreover, previous studies have linked honey bee immune status to lipid store gene expression profiling ( Mao et al 2013 ; Salmela et al 2015 ).…”
Section: Resultsmentioning
confidence: 95%
“…Future studies on lipid metabolism and the role of fat bodies on bee health are an important line of research and will benefit from additional genome-wide comparisons. C eratina calcarata is an emerging model species to understand the lipid metabolism and overwintering diapause and nutritional regulation of caste determination ( Rehan et al 2014 ; Durant et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, worker honey bees and leafcutter bees were collected at adult eclosion which encompasses the emergence of the insect from the pupal cell followed by expansion and hardening of the wings. All phases of this process represent an orchestrated hormonal interplay leading to what we know as the adult bee 48 50 . Prior to eclosion, midgut tissues have little structure, but become regionalized after adult emergence, remaining stable except when recovering from acute tissue damage 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased lipid stores allow larger females to better survive diapause (Tepedino and Torchio, 1982;Strassmann et al, 1984;Strohm and Linsenmair, 1999). Past research on C. calcarata found that lipid metabolism is upregulated in overwintering bees (Durant et al, 2016). Additionally, increased lipid stores have been linked to an increase in reproductive potential in Polistes metricus (Toth et al, 2009) and Apis mellifera (Toth and Robinson, 2005).…”
Section: Discussionmentioning
confidence: 99%